Effect of the partial input of the peeled and sifted cottonseeds in the feed mixture of the chicken on some productive and economic indicators (Journal of Hama University, 2019)
The research was carried out on 600 Broiler hybrid Hubbard. The chicks were cared for in a barn of the open model at the Institute of Agricultural Technology at Damascus University. The chicks were randomly distributed to eight replicates. The cottonseeds Meal of 5, 10, 15 and 25% was added to the first stage feed mixture, second, third, fourth consecutively for four replicates only. The obtained results indicate that the introduction of the peeled and sifted cottonseeds Meal at different varieties according to the age group to the fodder mix did not have a negative effect on all the studied productivity indicators. Live weight was not affected by the addition of squat and roasted cotton, although there was a slight reduction in live weight, whereas the weight increase was only increased in the third fodder stage by 3 g per bird. The cumulative weight increase was reduced by the end of the fattening period by 150 g for the bird. The value of the feed conversion factor was estimated during the whole fattening period (From 1 to 49 days) for the birds of the witness by 2.2 and the birds of the experiment by 2.4, and there were no significant differences in the simple and cumulative mortality rate at the end of each stage of the application period. The cost of substituting the substrate for peeled and soft cottonseeds was better at each stage of the various assignments. The cost of feed per bird for the whole feeding period decreased by 8.92 SP per bird, and decreased the cost of producing one kg live weight at the end of a period of fattening by 4.82 SP per kg .